Dimensi Teologis Pemulihan Imago Dei dan Implikasinya dalam Kehidupan Kristen - Juli Grehem; Yanti Desayo; Malik Bambangan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the theological concept of Imago Dei (Image of God) and its implications for the lives of believers. The formulation of the problem includes three aspects: general understanding of Imago Dei, theological review of the concept, and its application in the context of contemporary Christianity. Using qualitative methods and descriptive analysis approaches, data were collected through a literature study of relevant theological sources. The results of the study indicate that humans, as creatures created in the image and likeness of God, have intrinsic value, dignity, and responsibility as representations of God in the world. Although this image has been damaged by sin, through the redemptive work of Christ as the perfect Imago Dei, the image can be restored. This restoration occurs gradually through the process of justification, sanctification, and glorification, which leads believers towards Christlikeness. This study emphasizes the importance of a theological understanding of Imago Dei as the basis for ethics, spirituality, and identity of Christians in a complex and pluralistic world.